The house of silk [large type] : a Sherlock Holmes novel - Horowitz, Anthony, 1955- (Mulholland Books/Little Brown & Company, 2011)
It is 1890. A year after Holmes's death, Watson--now in a retirement home--narrates a tale of Sherlockian detection that could tear apart the very fabric of society. The story opens with a train robbery in Boston, and moves to the innocuous setting of Wimbledon.